Statement on the 2024 article of the year: Cybergrooming - an inventory and two conclusions: by Tom Kattenberg - Kaspar, Johannes (Kriminologie - das Online-Journal, 2025)
There is no secret recipe for a successful academic article, but - based on experience - there are a few ingredients that will contribute to its success: a current and interesting topic; clear and understandable language; an instructive review of the state of knowledge from the perspective of various disciplines; and – particularly important – new (including practical) approaches and ideas that encourage readers to think and perhaps even inspire other researchers to address the same topic. Tom Kattenberg’s text contains all of this and has therefore rightly been chosen as the article of the year for 2024.